(untitled) (Tanzania Journal for Population studies and Development, 2010)
Provision of equality in education at all levels is central in achieving development in any society. However, this situation is limited in Maasailand due to low response of Maasai parents and girl students towards secondary school education. The problem burdens this community and the nation at large in the provisions of girls’ access to Secondary Education (SE). In spite of government and NGOs efforts to address the issue, the problem is still persisting throughout pastoralist areas. If this situation is not addressed, is a danger of gender inequality in terms of access to education. Thus, the objective of this study is to determine factors causing low response of Maasai parents and girl students towards secondary education in Monduli district, and to generate empirical information on strategies to address the problem. The study randomly selected a total of 125 respondents who were interviewed using open and close-ended questionnaires. Data collected was coded and analyzed using Statistical Package for Social Sciences. The findings reveal that low response towards SE was influenced by parents’ education, occupation and marital status. Socio-cultural factors such as norms, values and nomadic life also limit access of girls’ SE. Based on the study findings, it was recommended that sensitization programmes, and special policies and strategies that promote girls’ access to education are required to raise awareness on the importance of girls’ education.